THE ROLE OF INTERNET MEMES AS A FRAGMENT OF MODERN CULTURE IN THE STUDY OF THE GERMAN LANGUAGE - Nakonechna , Lyubov (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is dedicated to the role of internet memes in the study of the German language, their functioning features, and ways of using them as fragments of contemporary culture, which are applied as effective tools and motivation in education. Special attention is given to well-known German-language memes in the internet space and their usage in various contexts. The influence of memes on the development of German vocabulary and grammar, as well as on the understanding of cultural aspects of the language, is analyzed. Personal contribution: researching the role of internet memes in language learning can be useful for students and teachers who seek to expand their knowledge and understanding of modern language practices. ____________ References: • Schmidt, J. «Memes in Germany: Politicized Humor in a Digital Age.» Journal of Folklore Research53 (3) (2016): 313-329. • Kavemann, B. «Merkel-Raute» im Netz – zur Visualisierung von Macht.» In B. Kavemann, F. Stuppert, & J. Peil (Eds.). Visuelle Politik: Theoretische und methodische Innovationen in der Politikwissenschaft (2019): 131-155. • Infratest dimap. Digitale Kommunikation 2019: Nutzungsverhalten und Trends [Digital Communication 2019: Usage and Trends], https://www.infratest-dimap.de/fileadmin/offset-Dimap-Studien/Digitale_Kommunikation_2019.pdf]. • The Local Germany. The German phrases you need to know when living in Germany (2018), https://www.thelocal.de/20180829/the-german-phrases-you-need-to-know-when-living-in-germany/ • The World of German Memes, FluentU.com • Using Internet Memes in the ESL Classroom, BusyTeacher.org • Understanding German Idioms Using Memes, GermanPod101.com